Transition radiation of the electron rotating in the diffuse plasma boundary - Musatenko, K.S.; Anisimov, I.O. (Вопросы атомной науки и техники, 2009)
The diffuse boundary model is suggested to describe the transition radiation of relativistic electrons drifting through
the interplanetary shock. The detailed description of the solution for electrons moving along the circular orbit is
presented. Maximum of the transition radiation spectrum calculated for one electron rotating in the diffuse plasma
boundary lies in the same frequency range as the electromagnetic emission detected by satellites’ devices. This result
justifies the assumption of the possible contribution of relativistic electrons transition radiation to the observed radiation. Для опису перехідного випромінювання релятивістського електрону, що дрейфує через міжпланетну ударну
хвилю, запропоновано модель розмитої границі плазми. Представлено детальний опис розв’язки для електрона,
що має кругову орбіту. Максимум спектру перехідного випромінювання одного електрона, що обертається в
розмитій границі плазми, знаходиться в тому ж частотному діапазоні, що і електромагнітне випромінювання,
що спостерегається супутниковими приладами. Цей результат підтверджує припущення про можливий внесок
перехідного випромінювання релятивістських електронів в спостережуване випромінювання. Для описания переходного излучения релятивистского электрона, дрейфующего через межпланетную
ударную волну, предложена модель размытой границы плазмы. Приводится детальное описание решения для
электрона, имеющего круговую орбиту. Максимум спектра переходного излучения одного электрона, который
вращается в размытой границе плазмы, находится в том же частотном диапазоне, что и наблюдаемое
спутниковыми приборами электромагнитное излучение. Этот результат подтверждает предположение о
возможном вкладе переходного излучения релятивистских электронов в наблюдаемое излучение.